A study of growth pattern and serum ferritin levels in transfusion-dependent thalassemic children on oral iron chelating agents (deferasirox) in King George Hospital, Visakhapatnam - Paidi, Satish Chandra; C., Sneha (International Journal of Contemporary Pediatrics, 2022)
Background: In India majority of thalassemia children are under transfused and receive insufficient chelation therapy. Only few researches on growth parameters from this region are available making it difficult to comprehend the loopholes of the disease and its treatment. Methods: It was a descriptive, prospective study of 50 cases of transfusion-dependent thalassemia children on oral iron chelator deferasirox observed during one year (November 2019-December 2021) at King George hospital, Visakhapatnam. Results: Most commonly affected were more than 6 years of age. 98% of the children had mean pre-transfusion hemoglobin of less than 8 g/dl with the temporal association of growth retardation. Weight (64%) was more affected than height (36%). Only 46% showed effective iron chelation after using deferasirox. Conclusions: 98% had low pre-transfusion hemoglobin and deferasirox alone was not an effective oral iron chelator resulting in growth retardation in the majority of children. Thalassemia that requires blood transfusions Children are at a high risk of developing morbidities such as growth retardation as a result of insufficient therapy. Many of them were the result of consanguineous marriage, suggesting the disease’s genetic basis. 98 percent of children had low pretransfusion hemoglobin of 7 gm%, with a mean of 6.5 gm%, showing that blood transfusions were insufficient. There were no side effects associated with the use of deferasirox and it alone proved ineffective in lowering serum iron excess, highlighting the need to combine it with novel modalities to improve its effectiveness. Growth retardation is a common ailment and low hemoglobin levels increased with age, showing hypoxia as a cause.